GROWTH PERFORMANCE AND LIVELIHOOD IN CULTIVATION OF VANNAMEI SHRIMP (Litopenaeus vannamei) IN INTENSIVE TAMBAK PT. ANDULANG SHRIMP FARM SUMENEP, EAST JAVA - Ritonga, Lusiana BR; Arifin, M. Zainal; Harijon, Teguh; Aonullah, Asep Akmal; Bawazir, Ach. Faizal Maulana (Politeknik Kelautan dan Perikanan Dumai, 2024)
Incentive shrimp farming system has become a farming system adopted by most Indonesian farmers to rapidly increase pond productivity with high stocking densities ranging from 100-300 fish/m2. The study aimed to determine the growth performance and survival rate of Vannamei shrimp culture at PT Andulang Shrimp Farm, Sumenep, East Java with different plot sizes and stocking densities. In the augmentation method, 2 culture plots are used, each with an area of plot D4 (1,932 m2) with a stocking density of 177 fish/m2 and plot F3 (2,600 m2) with a stocking density of 172 fish/m2. In plot D4, the average body weight (ABW) was 26.45 g, the feed conversion ratio (FCR) was 1.63 and the survival rate (SR) was 74.05% with a total harvest tonnage of 4,845.64 kg. In plot F3, the average body weight (ABW) was 26.36 g, the FCR was 1.61 and the SR was 75.42% with a total yield of 6,674.42 kg. A high protein diet contributes to the growth of Vannamei shrimp. Optimal water quality and proper feeding can promote the growth of Vannamei shrimp.